The structure of Ezra-Nehemiah as a literary unit - Hans-Georg Wuench (Verbum et Ecclesia, 2021)
The OT books, Ezra and Nehemiah, are to be considered as one book. This is more or less the common conviction of most OT scholars today. However, their redaction process raises many questions. What is their relation to the book of Chronicles, and how is their actual structure to be understood? Why do we find two almost identical lists of returnees from exile in Ezra 2 and Nehemiah 7? What about the differences between these lists? This article understands the structure of Ezra-Nehemiah as a consciously created literary unit, where the two lists of returnees serve as an important part of the literary structure. The author works on the assumption of the so-called new literary criticism, understanding the narrative in the book on a synchronic basis. He shows that the book of Ezra-Nehemiah can indeed be understood as one literary unit, and that the two lists of returnees function as a literary means to structure the book. There is therefore no need to ‘re-organise’ the narrated events in Ezra-Nehemiah according to an alleged different chronological order.